2005
DOI: 10.1128/iai.73.8.5256-5261.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Aerosolized Yersinia pestis Challenge following Homologous and Heterologous Prime-Boost with Recombinant Plague Antigens

Abstract: A Yersinia pestis-derived fusion protein (F1-V) has shown great promise as a protective antigen against aerosol challenge with Y. pestis in murine studies. In the current study, we examined different prime-boost regimens with F1-V and demonstrate that (i) boosting by a route other than the route used for the priming dose (heterologous boosting) protects mice as well as homologous boosting against aerosol challenge with Y. pestis, (ii) parenteral immunization is not required to protect mice against aerosolized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…However, adjuvants do more than just increase the magnitude of the immune response and the qualitative nature of the response is also important. We recently demonstrated that SC immunization with F1-V in the absence of an adjuvant can confer 70% protection against aerosol challenge with Y. pestis [13]. However, IN immunization in the absence of adjuvant resulted in 100% mortality while the inclusion of adjuvant in the formulation provided 90% protection, demonstrating that an adjuvant is necessary for protection following IN immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adjuvants do more than just increase the magnitude of the immune response and the qualitative nature of the response is also important. We recently demonstrated that SC immunization with F1-V in the absence of an adjuvant can confer 70% protection against aerosol challenge with Y. pestis [13]. However, IN immunization in the absence of adjuvant resulted in 100% mortality while the inclusion of adjuvant in the formulation provided 90% protection, demonstrating that an adjuvant is necessary for protection following IN immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant finding of that study is that boosting by a different (heterologous) route than the priming dose can be as or more effective than homologous boosting for induction of either serum or bronchioalveolar anti-F1-V IgG1 responses. In a follow-on aerosol challenge study [13], we demonstrated that the route of immunization and choice of adjuvant influence the magnitude of the antibody response as well as the IgG1/IgG2a ratio, and that inclusion of an appropriate adjuvant in the vaccine formulation is critical for protection against aerosol challenge following non-parenteral immunization.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming increasingly clear that mixing of vaccine routes can have a positive effect on both antibody production and protection. It has been previously reported that in F1-V vaccinations, heterologous prime-boost regimens are at least as effective as homologous boost regimens for inducing serum anti-F1-V IgG1 responses (29,30). In this study, all vaccinated mice received an initial s.c. injection, which effectively induced a potent systemic humoral response (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…delivered FI-BRSV vaccine in mice (32). Since there is evidence that combinations of mucosal and parenteral administration lead to immune responses that were as strong or stronger than those resulting from either mucosal or parenteral immunization alone (21,22,29,30), the purpose of this study was to determine the effects of the route of delivery on antibody, mucosal, and cell-mediated immune responses, as well as protection against BRSV. We compared i.n.…”
mentioning
confidence: 99%